2004
DOI: 10.1021/ja0473283
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State17O NMR as a Probe for Structural Studies of Proteins in Biomembranes

Abstract: A key experimental challenge to understand conformational details of membrane proteins is to provide unambiguous atomic-scale information about the molecular bonding arrangement and any changes that occur upon receptor activation. This demands the development of experimental probe techniques to deliver this information of biological and pharmaceutical importance. Solid-state NMR is a nonperturbing approach which can be used to study ligandprotein interactions where molecular size is not limiting and crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 17 publications
4
55
0
Order By: Relevance
“…Later, Oldfield and co-workers [4] successfully obtained solid-state 17 O NMR spectra for [C 17 O]myoglobin (16.7 kDa per ligand) under conditions of magic-angle spinning (MAS) at 11.7 T. Several groups have since reported solid-state 17 O NMR spectroscopic studies of membrane-bound peptides. [5][6][7] Herein we report the first comprehensive solid-state 17 17 O spin-lattice relaxation times (T 1 ) in these solid protein-ligand complexes are typically on the order of several milliseconds; therefore, very rapid data collection is possible. Furthermore, we found that several sensitivity-enhancement methods uniquely suited for halfinteger quadrupolar nuclei, such as double-frequency sweep (DFS), [8] rotor-assisted population transfer (RAPT), [9] and hyperbolic secant (HS) pulses, [10] can be used to obtain highquality solid-state 17 O NMR spectra for large protein-ligand complexes.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Later, Oldfield and co-workers [4] successfully obtained solid-state 17 O NMR spectra for [C 17 O]myoglobin (16.7 kDa per ligand) under conditions of magic-angle spinning (MAS) at 11.7 T. Several groups have since reported solid-state 17 O NMR spectroscopic studies of membrane-bound peptides. [5][6][7] Herein we report the first comprehensive solid-state 17 17 O spin-lattice relaxation times (T 1 ) in these solid protein-ligand complexes are typically on the order of several milliseconds; therefore, very rapid data collection is possible. Furthermore, we found that several sensitivity-enhancement methods uniquely suited for halfinteger quadrupolar nuclei, such as double-frequency sweep (DFS), [8] rotor-assisted population transfer (RAPT), [9] and hyperbolic secant (HS) pulses, [10] can be used to obtain highquality solid-state 17 O NMR spectra for large protein-ligand complexes.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…This labeling was used because the COOgroups have been shown to be distinguishable from one another by solid-state NMR measurements. 16 Finally the COO -groups and the NH 3 + group on each glutamic acid molecule were allowed to rotate in the model about the appropriate C-C or C-N bond.…”
Section: Experimental and Modeling Proceduresmentioning
confidence: 99%
“…Solid-state NMR spectroscopy of 17 O is a powerful tool to study hydrogen bonds since the 17 O chemical shift and quadrupolar coupling are claimed to be very sensitive to the strength and geometry of the hydrogen bonds. In recent years, several groups have demonstrated the feasibility of 17 O NMR experiments in small organic molecules, [3][4][5][6] nucleic acid basis, 7 amino acids, 3,6,[8][9][10] polypeptides, 11,12 and proteins, 13,14 showing a correlation between hydrogen bonding and 17 O chemical shifts and quadrupolar couplings. 17 O is a quadrupolar nucleus (S ) 5 / 2 ) with a low sensitivity and a low natural abundance.…”
Section: Introductionmentioning
confidence: 99%